2022
DOI: 10.1111/epi.17217
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning approaches for imaging‐based prognostication of the outcome of surgery for mesial temporal lobe epilepsy

Abstract: Objectives Around 30% of patients undergoing surgical resection for drug‐resistant mesial temporal lobe epilepsy (MTLE) do not obtain seizure freedom. Success of anterior temporal lobe resection (ATLR) critically depends on the careful selection of surgical candidates, aiming at optimizing seizure freedom while minimizing postoperative morbidity. Structural MRI and FDG‐PET neuroimaging are routinely used in presurgical assessment and guide the decision to proceed to surgery. In this study, we evaluate the pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 37 publications
0
26
1
Order By: Relevance
“…The differences in FR × T could reflect more accurate EZ localization and subsequent higher possibility of complete resection. A recent prognostic study on mesial TLE proposed that the percent of temporal lobe hypometabolism resected was crucial for predicting outcome 46 . However, we did not replicate such results, which might be explained by the mixed seizure type cohort and differences in technique.…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…The differences in FR × T could reflect more accurate EZ localization and subsequent higher possibility of complete resection. A recent prognostic study on mesial TLE proposed that the percent of temporal lobe hypometabolism resected was crucial for predicting outcome 46 . However, we did not replicate such results, which might be explained by the mixed seizure type cohort and differences in technique.…”
Section: Discussioncontrasting
confidence: 90%
“…A recent prognostic study on mesial TLE proposed that the percent of temporal lobe hypometabolism resected was crucial for predicting outcome. 46 However, we did not replicate such results, which might be explained by the mixed seizure type cohort and differences in technique. Of interest, the specific histopathological abnormality pathologies vs nonspecific subgroup analysis also showed that the negative correlation no longer existed in the nonspecific pathologies group, which are usually considered to be associated with poorer surgical outcome.…”
Section: Discussionmentioning
confidence: 63%
“…Previous studies that have used both machine learning techniques and traditional statistical modelling approaches to predict post-operative seizure outcome have found that logistic regression models perform as well as, or even better than, machine learning ones. 11,15,22 To our knowledge, only one study by Yossofzai et al . 23 has found that a machine learning model outperforms a logistic regression; however, this was a 0.1-0.2 difference in AUC (0.72 versus 0.73 in the train dataset; 0.72 versus 0.74 in the test dataset).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of these models have, however, been trained on relatively small sample sizes (N < 100) [7][8][9][10][11][12][13][14][15][16][17][18] and therefore have a high risk of 'overfitting' (a model overfits when it models the training dataset too closely, performing well on this dataset but consequently underperforming on new, 'unseen' datasets). 19,20 Model training sets have also been comprised almost exclusively of temporal lobe surgery patients 7,8,[10][11][12][13]15,17,18,21,22 , often relied on post-surgical factors 11,12,14,23 , and frequently utilized post-processing neuroimaging analyses that cannot be readily replicated by others. 7,[9][10][11]13,[16][17][18]21 As such, many existing models may be difficult to incorporate into routine pre-surgical evaluation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation